Francisco de la Maza. Sor Juana Inés de la Cruz ante la historia. Pról. de Elías Trabulse. México : UNAM, 1980. 612 p. - González, María Cristina (El Colegio de México, 1982)
Se reseñó el libro: Sor Juana Inés de la Cruz ante la historia.